“Toeing the line” - Udovič, Boštjan (Annales. Series historia et sociologia, 2024)
This paper seeks to underscore the significance of Grlica as a pivotal journal for youth music in Slovenia from 1953 to 1988. It explores how Grlica played a crucial role in conveying the ideological and socio-political aspects of the socialist system prevalent during that period. Applying historical-developmental and historical-comparative methods, the paper presents three key findings. Firstly, Grlica was primarily a professional journal, with little to no ideological components. Secondly, the ones we do find were predominantly present in the initial period of Grlica’s publication, i.e., until 1965, becoming increasingly rare as time wore on. Thirdly, composers who published their works in Grlica held diverse ideological and musical orientations, indicating that Grlica was not only a professional journal but also characterised by broad-minded and open perspectives.
Keywords: glasba za mladino; ideologija; ideology; journals; journals for youth; mladinska glasba; revije; revije za mladino; socialism; Socialistična družba; socializem; youth music